ANALISIS NILAI PENDIDIKAN KARAKTER PADA NOVEL REMBULAN TENGGELAM DI WAJAHMU KARYA TERE LIYE DAN PEMANFAATANNYA UNTUK BAHAN AJAR SMA KELAS X - Dede Siti Nurkhayati; Masrurih; Maskur Subaweh, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the character education values contained in the novel Rembulan Tenggelam di Wajahmu by Tere Liye, published by Republika in 2009, and to explore its potential use as teaching material for senior high school (SMA) students. The research employs a qualitative method, with data collected through document analysis (recording) of the novel Rembulan Tenggelam di Wajahmu by Tere Liye. The researcher recorded data obtained from documentation as the primary data source for the study, and validated the teaching material using the researcher as the research instrument. This means the researcher conducted repeated readings and analyses of the data source. The data analysis techniques used in this study are as follows: a) analyzing the character education values present in the novel Rembulan Tenggelam di Wajahmu by Tere Liye, b) identifying and recording words and sentences that contain character education values in the novel, and c) noting, collecting data related to the research, and drawing conclusions from the study.